Leading outside the lines : how to mobilize the (in)formal organization, energize your team, and get better results - Katzenbach, Jon R., 1932- (Recorded Books, 2020)
An all-new approach to understanding and inspiring the (in)formal connections of an organization In this dynamic work, thought leaders Jon R. Katzenbach, coauthor of the business classic The Wisdom of Teams, and Zia Khan offer an all-new examination of the modern workplace, and how leaders and managers must embrace it for success. Together they reveal how two distinct factions form the bigger picture for how organizations actually work: the more defined and visible "formal organization" of a company--the management structure, performance metrics, and formal strategy--and the "informal organization"--The culture, social networks, and ad hoc communities that spring up naturally and, in an equally vital but different way, can accelerate or hinder an organization's success. Through compelling case studies from enterprises around the world (in business, government, the nonprofit sector, and academia) Katzenbach and Khan explore how top-level organizations balance the informal and formal elements of organizations to achieve outstanding results. Leading Outside the Lines takes a timeless organizational approach and creates a powerful paradigm-shifting tool set for applying it, showing when you can get the most done by using the informal elements that operate under the radar, and when it is in fact better to use formal processes. Most important, it illustrates how the two can work together to get the best of both. This groundbreaking book also offers self-assessment guidelines for senior leaders, front-line managers, and individual contributors who need to get better performance results. Insightful leaders and managers at all levels know that to really lead an organization, you cannot rely on formal constructs alone; you have to use the informal elements as well. Using the information and tools outlined in this compelling book, leaders and potential leaders at all levels can tap into the power of the informal to achieve superlative performance and results